Operative Management of Anastomotic Leaks after Colorectal Surgery - Saur, Nicole M.; Paulson, E. Carter (Clinics in Colon and Rectal Surgery, 2019)
Anastomotic leak is associated with increased morbidity and mortality after colorectal surgery. Although surgical techniques have improved over time, anastomotic leak is still a reality in colorectal surgery with rates ranging from as low as 1% for low-risk anastomoses, such as enteroenteric or ileocolic, to 19% for high-risk coloanal anastomoses. There are many varied risk factors for anastomotic leak. However, many of the risk factors have not been definitively proven in high-quality studies. Presumably, risk factors are cumulative and every effort should be made to optimize modifiable risk factors in the perioperative period. Treatment of anastomotic leak should start with the determination of patient stability followed by resuscitation and diagnostic imaging or operative exploration. Operative findings will dictate surgical approach with the goal of controlling sepsis and stabilizing the patient. If nonoperative treatment is undertaken, close patient monitoring is necessary to ensure control of sepsis and that intervention is undertaken if the clinical picture changes. Early intervention at each stage is key to decreasing the morbidity of anastomotic leak.
Keywords: anastomosis; leak; sepsis; drainage; exploration